MSMES Competitiveness Strategies During Covid 19 Pandemic Using Technoprenurship Approach - Miftahul Huda; Muhammad Fu'ad; Nabila Eka Fitri Azzahra; Nova Prihastuti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This study aims to identify and analyze strategies that MSMEs can apply to increase the competitiveness of superior products during the COVID-19 pandemic by taking a technopreneurship approach. The method used in this research is a qualitative case study ie, research that focuses intensively on one particular object studied as a case. The object of this research is MSMEs registered at the Departement of Coorperative and Micro Enterprises of Pasuruan Regency many as four MSMEs as samples. The results obtained from this study indicate a need for approaches and strategies that utilize technology to be more creative and innovative so that a business can survive and compete during this pandemic.